A coddling of the sagittal suture: inequality in spring-assisted expansion - Ng, Jinggang J.; Chang, Ashley E.; Villavisanis, Dillan F.; Shakir, Sameer; Massenburg, Benjamin B.; Wu, Meagan; Romeo, Dominic J.; Swanson, Jordan W.; Bartlett, Scott P.; Taylor, Jesse A. (Child's nervous system, 2024)
Purpose We examined differences in long-term morphometric outcomes of spring-mediated cranioplasty (SMC) for various forms of isolated nonsyndromic sagittal craniosynostosis. Methods A retrospective review was performed of children who underwent SMC from 2011 to 2020 at the Children’s Hospital of Philadelphia. Cephalic indices (CI), Whitaker grades, parietal bone thickness, and degree of suture fusion were assessed. Frontal bossing and vertex-nasion-opisthocranion (VNO) angles were compared to a normal control group. Results Fifty-four subjects underwent surgery at age 3.6 ± 1.0 months with follow-up of 6.3 ± 1.8 years. Mean CI was 75.2 ± 4.1 at 5.9 ± 2.0 years postoperatively. Mean CI were 75.8 ± 4.1 ( n = 32), 76.4 ± 4.0 ( n = 22), and 77.1 ± 4.8 ( n = 11) at 5, 7, and 9+ years postoperatively, respectively. Three (5.6%) required reoperation for persistent scaphocephalic cranial deformity. Fifty-one (94.4%) were Whitaker Grade I. On physical examination, 12 (22.2%) demonstrated craniofacial abnormalities. At long-term follow-up, there were no differences in frontal bossing angle (102.7 ± 5.2 degrees versus 100.7 ± 5.6 degrees, p = .052) and VNO angle (44.9 ± 3.3 degrees versus 43.9 ± 2.2 degrees, p = .063) between study and control groups. Younger age at surgery predicted a lower Whitaker grade, more normalized VNO angle, and greater change in CI during active expansion. Increased percentage fused of the posterior sagittal suture predicted a higher Whitaker grade, while decreased anterior fusion was associated with frontal bossing and temporal hollowing. Conclusions Overall, children undergoing spring-mediated cranioplasty for sagittal craniosynostosis demonstrated maintenance of CI, favorable cosmetic outcomes, and a low reoperation rate at mid-term follow-up. Early intervention is associated with improved aesthetic outcomes, and regional fusion patterns may influence long-term craniofacial dysmorphology.